Convergent-close-coupling calculations for excitation and ionization processes of electron-hydrogen collisions in Debye plasmas - Zammit, M.; Fursa, Dmitry; Bray, Igor (American Physical Society, 2010)
Electron-hydrogen scattering in weakly coupled hot-dense plasmas has been investigated using the convergent-close-coupling method. The Yukawa-type Debye-Hckel potential has been used to describe the plasma screening effects. The target structure, excitation dynamics, and ionization process change dramatically as the screening is increased. Excitation cross sections for the 1s-2s,2p,3s,3p,3d and 2s-2p,3s,3p,3d transitions and total and total ionization cross sections for the scattering from the 1s and 2s states are presented. Calculations cover the energy range from thresholds to high energies (250 eV) for various Debye lengths. We find that as the screening increases, the excitation and total cross sections decrease, while the total ionization cross sections increase.